2015
DOI: 10.1142/s0218495815500077
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Quality Management Practices and Its Pattern Analysis in Indian Service SMEs

Abstract: Substantial research exists on quality management practices in context to large organisations with plethora of studies in manufacturing organisations while exiguously aiming service sector SMEs. As more and more organisations strive to remain competitive, the concepts and practices of quality management have received increased attention by Indian industry. The contribution of service sector in Indian economy has increased at a faster rate in comparison with other sectors. Considering the pressing need this res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 130 publications
0
11
0
Order By: Relevance
“…From this perspective the effect of QM practices on performance depends on the level of certain contextual factors (third variable)". From in-depth interview as discussed earlier, we take IT and EC as organisational resource capability to be the two contextual factors (Basu and Bhola, 2015). Research has shown that QM plays an important role in improving firm's competitive positions and that application of IT influence this relationship (Willcocks et al, 2007).…”
Section: Impact Of Qmpmentioning
confidence: 99%
“…From this perspective the effect of QM practices on performance depends on the level of certain contextual factors (third variable)". From in-depth interview as discussed earlier, we take IT and EC as organisational resource capability to be the two contextual factors (Basu and Bhola, 2015). Research has shown that QM plays an important role in improving firm's competitive positions and that application of IT influence this relationship (Willcocks et al, 2007).…”
Section: Impact Of Qmpmentioning
confidence: 99%
“…For example, the entrepreneurial vision, capabilities and activities, alone, will not be enough to achieve success, unless there is a quality management philosophy in the organization (Al-Dhaafri et al , 2016). With more and more manufacturing firms striving to remain competitive, the concepts and practices of quality management have received increased attention by the Indian manufacturing sector (Basu and Bhola, 2015). Under the pressure of present global competitive environment, for a manufacturing firm, it is being more difficult to exceed their rivals and outperform.…”
Section: Introductionmentioning
confidence: 99%
“…Operational activities in producing coconut shells, producers do not diversify their products and each producer only produces one kind of product that is the same as other producers, and the producers are satisfied with the coconut shell products they produce. 7. Human resource management activities, existing workers tend to only do the work assigned to them without any desire to create product diversification.…”
Section: Several Activities In the Coconut Shell Agro-industry Inmentioning
confidence: 99%
“…Especially, Since all businesses (especially large) have theirbsuppliers from whom they buy either materials or products, the quality that they provide them is able to affect the overall quality of the finished products [6]. As organisations is considered to be one of the most admired and robust operations management tool which despite of several criticism attained colossal importance from both academic and industry [7]; [8]; [9]; [10]; [11]; [12]; [13]. The data collected through the Forum Group Discussion (FGD) is in the form of identification of potentials that can be developed, especially the development of local potential, especially with regard to coconut shells related to the supply of raw materials to the marketing of processed coconut shell handicraft products, as well as accommodating their aspirations.…”
Section: The Process Of Empowering Coconut Shells In Wager Hamlet Sukosari Village Kasembon District Mentoring Planningmentioning
confidence: 99%